An evaluation of the impact of IFRS 15 on JSE-Listed companies - Silva, Lolanda De Sa (My University, 2017)
The purpose of this paper is to evaluate the operational impact an accounting change will have on organisations. This paper looks specifically at the impact the operationalisation of International Financial Reporting Standard 15 (IFRS 15) will have on Johannesburg Stock Exchange-listed (JSE-listed) organisations with the objective of determining whether it will result in changes only to financial reporting or whether it will also impact other aspects of the business. The research undertaken has relied on primary data collected from 20 recorded interviews with technical specialists, academics and preparers to determine the expected or actual change that IFRS 15 will bring about within an organisation. The findings suggest that the implementation of IFRS 15 will have far-reaching implications for the organisation, over and above financial reporting. It will bring about change within five main areas, including strategy, level of collaboration, training, information technology systems and the performance evaluation of employees and organisations. This paper contributes to the accounting literature on the process of implementing accounting changes and the resistance with which these accounting changes are encountered.
A research report submitted by Iolanda De Sa Silva Student number: 714327, 2017